"Swim with the Current, Stand like a Rock": Non-Traditional Age Undergraduates Coping with Racial Microaggressions. Issue 2 (4th May 2018) - Vaccaro, Annemarie; Ramirez, Amanda
Abstract : A qualitative case study with 18 non-traditional age undergraduate Women of Color yielded rich data about strategies they employed to cope with racial microaggressions on a predominantly White campus. Women first decided if, and how, to "pick their battles" based on how much time and emotional energy they had left after fulfilling familial and full-time employment responsibilities. Then, they drew upon six different coping strategies to respond to racial microaggressions. Implications and recommendations are provided.